All Days 2015
DOI: 10.2118/173873-ms
|View full text |Cite
|
Sign up to set email alerts
|

Flow Control Optimisation to Maximise the Accuracy of Multi-phase Flow Rate Allocation

Abstract: The value added by intelligent wells (I-wells) derives from real-time, reservoir and production performance monitoring together with zonal, downhole flow control. Unfortunately, downhole sensors that directly measure the flow rates and phase cuts required for optimal control of the well's producing zones are not normally installed. Instead, Multi-zone, Multi-phase Flow Metering (MFM) parameters are calculated from indirect measurements (e.g. from zonal pressures, temperatures, and well flow rates).To-date all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Although only water breakthrough occurs in this synthetic case study, the formulations of fluid flow across the ICVs and wellbore can be modified to include the effect of gas flow rate caused by gas breakthrough. This adds the calculation of in situ gas mass fraction into the algorithm of estimation of zonal properties in addition to zonal reservoir pressure, zonal productivity index and zonal water-cut (Malakooti et al 2015). Malakooti et al (2015) also showed the applicability of MPFR workflow in gas reservoirs in which estimation of reliable values of reservoir parameters was difficult due to nonlinearity and extra unknowns in the inflow back-pressure equation.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Although only water breakthrough occurs in this synthetic case study, the formulations of fluid flow across the ICVs and wellbore can be modified to include the effect of gas flow rate caused by gas breakthrough. This adds the calculation of in situ gas mass fraction into the algorithm of estimation of zonal properties in addition to zonal reservoir pressure, zonal productivity index and zonal water-cut (Malakooti et al 2015). Malakooti et al (2015) also showed the applicability of MPFR workflow in gas reservoirs in which estimation of reliable values of reservoir parameters was difficult due to nonlinearity and extra unknowns in the inflow back-pressure equation.…”
Section: Resultsmentioning
confidence: 96%
“…This paper presents an ICM algorithm that designs the optimum number of flow tests required to simultaneously monitor the reservoir properties and (reactively) control the well's production. The MPFR, soft-sensing algorithm (Malakooti et al 2015), was our initial work in this area. The MFPR algorithm analyses use the measured data from an initial (n + 1) flow tests in an n-zone I-well to estimate the flow rate and phase fraction of the fluids being produced from each of the of the n zones.…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations